Descriptive Study of Patients Referred for Colonoscopy at Gastro-enterology Unit at Al-Imamain Al-Kadhemain Medical City in Baghdad - Abdulhassan, Bashar A.; Mahdi, Qahtan A.; Meeshal, Mushtaq T.; Ali, Muhammed H.; Kadhim, Sajjad M. Ali; Noori, Ali (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Colonoscopy is a critical and frequently used medical procedure that is essential in identifying colonic and rectal cancers on time. It remains the preferred method for visualizing the colonic and rectal mucosae, enabling the detection of conditions like carcinoma, adenoma, and inflammation. Colorectal cancer is the third most common cancer worldwide, and due to its tendency to present late, screening programs that rely on a sensitive tool like colonoscopy are of utmost importance. Objectives: To evaluate the clinical characteristics and colonoscopic findings, including colorectal cancer, among patients referred to the gastro-enterology unit in Al-Imamain Al-Kadhemain Medical City and determine the most common presenting symptoms of colorectal diseases. Patients and Methods: A study was conducted at the GIT unit of Al-Imamain Al-Kadhemain Medical City from November 2022 to March 2023 involving 120 patients who underwent colonoscopy. The study recorded the presenting complaint and colonoscopy results. The mean and standard deviation were used to express continuous variables, while frequency and percentage were used for categorical variables The difference between means was tested using Welch’s t-test, and a P-value less than 0.05 was considered statistically significant. Result: The study included a total of 120 participants, with an average age of 46.57 years. The leading indication for colonoscopy was bleeding per rectum (45%), followed by chronic constipation (26.6%) and chronic abdominal pain (21.6%). The most common pathologies observed during colonoscopy were internal hemorrhoid (18.3%), polyposis (15%), and colorectal cancer (13.3%). Conclusion: Rectal bleeding is the primary reason for conducting colonoscopy and is also the most common symptom of colorectal cancer. During colonoscopy, Internal hemorrhoids are frequently observed, which is the most common cause of rectal bleeding. Polyps and colorectal cancer are the next most frequent causes of rectal bleeding.